Analisis Hubungan Corporate Governance, Corporate Social Responsibility, dan Corporate Financial Performance pada Perusahaan Kompas 100 - Caesari, Annisa Putri; Irwanto, Abdul Kohar; Syamsun, Muhammad (Universitas Brawijaya, Indonesia, 2016)
In accommodating the objectives and obligations, the company may apply a systemÂ called Corporate Governance (CG) and Corporate Social Responsibility (CSR). TheÂ implementation of CG and CSR are related because CSR is a consequence of the implementationÂ of CG. CG and CSR are also interconnected with Corporate Financial PerformanceÂ (CFP). Through the implementation of CG, the company can improve CFP. While the relationshipÂ between CSR and CFP can be associated positively or negatively. CSR can improveÂ CFP during the company does not over investment in CSR activities. The research wasÂ conducted on one hundred companies listed in Kompas100 index to determine the relationshipÂ of implementation of CG on the disclosure of CSR, the relationship of implementation ofÂ CG to the CFP, the relationship disclosure of CSR to the CFP, and the relationship of implementationÂ of CG to the CFP with CSR as a moderating variable in the sample companies.Â structural equation modeling (SEM) analysis uses in order to determine the relationship ofÂ these three variables. The results show that the implementation of CG which is reflected inÂ board size indicator significantly positive related to the disclosure of CSR activities. However,Â the implementation of CG significantly negative related to the company's financialÂ performance that is reflected in PER ratio. Moreover, CSR disclosure is significantly negativeÂ related to the financial performance. Due to the relationship between CG and CFP andÂ the relationship between CSR and CFP is significantly negative related, implementation ofÂ CG is also significantly negative related to the CFP through the disclosure of CSR as aÂ moderating variable.